Penerapan Prinsip Kepemimpinan Hamba dalam Markus 10:42-45 terhadap Tantangan Volatilitas Organisasi Gereja Kontemporer di Indonesia - Devyanti Kala'tasik; Dirgayanti Deka Semba’ Padang; Jemmi Jemmi; Juwita Suci Palembang; Resti Tomentang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Contemporary church organizations in Indonesia face a phenomenon of volatility characterized by fluctuations in congregation membership, persistent internal conflicts, external pressures from changing times, and a crisis of trust in its leaders. There is a significant gap between the theological idealism of servant leadership as taught in Mark 10:42-45 and the reality of leadership practices in the field, which often tend to be authoritarian, conflict-driven, and underserved. This study aims to analyze the application of the principle of servant leadership based on Mark 10:42-45 as a solution to face the challenge of the volatility of contemporary church organizations in Indonesia. The goal is to identify volatility challenges, analyze leadership practice gaps, and formulate effective servant leadership implementation models to restore trust and achieve sustainable congregation growth. This study uses a qualitative research method with a library research approach. Data from various literature sources were analyzed in depth to synthesize the theological concept of servant leadership with organizational management theory and the practical context of the church in Indonesia. The results of the study show that servant leadership is an effective solution to the volatility of the church. It was found that the main challenges in its implementation were hierarchical organizational culture and resistance to change. As a solution, this study formulates a model of servant leadership integration built on four pillars: strong spiritual foundations, adaptive leadership, collaborative governance, and continuous learning. The implementation of this model is through practical strategies such as transparency, empowerment of the congregation.